Integrating BIM with RFID technology to develop an onsite precast element management system - Nguyen, Thi Hoai Thanh (2016)
Construction material management has been identified by many industry professionals and researchers as one of the most important functions in a construction project, as a project’s bottom line is significantly reliant on good material management. The recent shift of the industry towards precast construction and just-in-time precast delivery presents the challenge and opportunity to improve the construction material management best practices so as to meet the demands of the current times. While BIM has been instrumental in improving productivity across the construction industry, the use of BIM is still limited to the design phase and to satisfy mandatory submissions in Singapore. However, BIM has the potential to enhance project management processes in the later phases of the project life, including precast concrete logistics management, if more dimensions of information are incorporated and managed in BIM. This study looks into the feasibility of combining both RFID – a proven technology widely used in other industries, and BIM – an underutilized technology in the Singapore construction scene, to improve the precast management process. This report summarizes the review of previous studies on the effectiveness of RFID implementation in other industries as well as in construction, and on the feasibility of BIM-RFID integration. Upon learning from the previous works, this project proposes an onsite precast management system assisted by BIM-RFID integration for a real life case study project (Signature at Yishun executive condominium by Kimly Construction). A prototype of the system architecture is then built and tested. While the prototype test results show evidences of the well-documented limitations of RFID technology in the construction environment, they also indicate that the performance of one of the RFID devices used in the system was sufficient for the requirements of the case study project. It was also concluded that the BIM-RFID integrated precast management system is technologically feasible and easily buildable.